Evaluation for Screening of Cervical Cancer by Visual Inspection with Acetic Acid (VIA) Method - Thapa, Kalpana Kumari; Parajuli, Urmila (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate pre-cancer lesion and presence of risk factors by visual inspection with acetic acid.Methods: A retrospective study was done to evaluate VIA positive women by demographic and reproductive history and presence of risk factors from the period 16th March, 2016 to 15th March, 2017.Results: A total of 605 women were included and counseled for screening mean age of patient in year's was 39.46±9.4 years and VIA positive rate was 4.63% (28/605).Conclusions: Cervical pre-cancer and cervical cancers were detected by VIA testing.